A Review of Equine Sleep: Implications for Equine Welfare - Greening, Linda; McBride, Sebastian (Frontiers in Veterinary Science, 2022)
Sleep is a significant biological requirement for all living mammals, due to its restorative properties and its cognitive function in memory consolidation. Sleep is a ubiquitous characteristic amongst mammalian species, however there are a number of differences between the sleep profiles of different species based upon a range of biological and environmental factors. It is therefore important to understand these differences given the importance of sleep to physical and psychological wellbeing and thus overall welfare of the animal. This review focuses specifically on the domestic horse and aims to consolidate current information on equine sleep, in relation to other species, in order to a) identify what constitutes normal sleep in the horse in terms of both quantity and quality, b) identify the best ways to measure equine sleep logistically and for the purpose of accuracy, c) to determine whether changes in equine sleep quantity and quality reflect changes in the animal’s welfare, and d) the primary factors that affect the quantity and quality of equine sleep. The review then identifies gaps in current knowledge and uses this information to identify and set the direction of future equine sleep research with the ultimate aim of improving equine performance and welfare. The conclusions from this review are also critically important in the context of current discussions around the ‘social license’ of horse use from a welfare perspective.